| library; |
| import self as self; |
| import "dart:core" as core; |
| |
| typedef E1<unrelated T extends core::Object* = dynamic> = () →* void; |
| typedef E2<unrelated T extends core::num*> = () →* void; |
| typedef E3<unrelated T extends core::Object* = dynamic, unrelated S extends core::Object* = dynamic> = () →* void; |
| typedef E4<unrelated T extends core::num*, unrelated S extends core::num*> = () →* void; |
| typedef E5<unrelated T extends S* = core::num*, unrelated S extends core::num*> = () →* void; |
| typedef E6<unrelated T extends core::num*, unrelated S extends T* = core::num*> = () →* void; |
| typedef F1 = <T extends core::Object* = dynamic>() →* void; |
| typedef F2 = <T extends core::num* = dynamic>() →* void; |
| typedef F3 = <T extends core::Object* = dynamic, S extends core::Object* = dynamic>() →* void; |
| typedef F4 = <T extends core::num* = dynamic, S extends core::num* = dynamic>() →* void; |
| typedef F5 = <T extends S* = dynamic, S extends core::num* = dynamic>() →* void; |
| typedef F6 = <T extends core::num* = dynamic, S extends T* = dynamic>() →* void; |
| typedef G1<invariant X extends core::Object* = dynamic> = <T extends X* = dynamic>() →* void; |
| typedef G2<invariant X extends core::num*> = <T extends X* = dynamic>() →* void; |
| typedef G3<invariant X extends core::Object* = dynamic, invariant Y extends core::Object* = dynamic> = <T extends X* = dynamic, S extends Y* = dynamic>() →* void; |
| typedef G4<invariant X extends core::num*, invariant Y extends core::num*> = <T extends X* = dynamic, S extends Y* = dynamic>() →* void; |
| typedef G5<invariant X extends core::num*> = <T extends S* = dynamic, S extends X* = dynamic>() →* void; |
| typedef G6<invariant X extends core::num*> = <T extends X* = dynamic, S extends T* = dynamic>() →* void; |
| typedef H1 = (<T extends core::Object* = dynamic>() →* void) →* void; |
| typedef H2 = (<T extends core::num* = dynamic>() →* void) →* void; |
| typedef H3 = (<T extends core::Object* = dynamic, S extends core::Object* = dynamic>() →* void) →* void; |
| typedef H4 = (<T extends core::num* = dynamic, S extends core::num* = dynamic>() →* void) →* void; |
| typedef H5 = (<T extends S* = dynamic, S extends core::num* = dynamic>() →* void) →* void; |
| typedef H6 = (<T extends core::num* = dynamic, S extends T* = dynamic>() →* void) →* void; |
| static field <T extends core::Object* = dynamic>() →* void f1; |
| static field <T extends core::num* = dynamic>() →* void f2; |
| static field <T extends core::Object* = dynamic, S extends core::Object* = dynamic>() →* void f3; |
| static field <T extends core::num* = dynamic, S extends core::num* = dynamic>() →* void f4; |
| static field <T extends S* = dynamic, S extends core::num* = dynamic>() →* void f5; |
| static field <T extends core::num* = dynamic, S extends T* = dynamic>() →* void f6; |
| static method main() → dynamic {} |